Disorder of Spanish verbs usage in the production of grammatical sentences based on pictures - Mohd Nor, Mariyati; Mansor, Nor Shahila (Human Resource Management Academic Research Society, 2020)
The aspect of verbs is one of the grammatical aspects that is more complex than the other word classes in learning Spanish as a foreign language. This happens because Spanish is a synthetic relative language that has a high inflection level on verb conjugation. The differences between the verb system in Spanish and the students’ native language cause confusion to the students in producing grammatical sentences in writing and lead to error. This study focused on the disorder and verb errors encountered by students in producing Spanish sentences. The respondents consisted of 30 students taking Spanish level I course at Sultan Idris Education University, Perak (UPSI). This study used the descriptive qualitative method with the application of the Taxonomy of Errors by Dulay, Burt & Krashen (1982) to analyse the data. The results of the study showed that verb disorder occurred particularly on the various forms of verb conjugation based on the subject (doer) and number, the use of verb Ser, Estar, Tener, and reflexive verb of Gustar. This confusion caused grammatical errors, ungrammatical sentences, the addition of unnecessary verbs, reduction of the important elements, incorrect verbs selection, and inaccurate order in sentence construction.